CONSIDERING BOSTON CONSULTING GROUP'S MATRIX OF STRENGTHENING COMPETITIVENESS AND GOOD GOVERNANCE IN INDONESIA:: A LITERATURE REVIEW PERSPECTIVE - Benny R.P. Sinaga (Scientia Integritas Utama, 2022)
The government must address several problems through good governance of tin mining companies in Indonesia in connection with tin reserves in Indonesia which are expected to run out in the next ten years. This study is sufficient to use a literature review to answer the existing problems. It was concluded that the reduced competitiveness of tin mining companies in specific years and the many obstacles they faced could be corrected by implementing the Boston Consulting Group (BCG) Matrix strategy.